Synthesis and Surface Activities of a Silicone Based Ester Quaternary Amine and Optimization of Synthesis Conditions by Response Surface Method - Cheng Zheng; Wuhuan Huang; Peng Chen; Taoyan Mao; Jing Lin; Qiming Yu (The Global Environmental Engineers, 2017)
A novel silicone based ester quaternary ammonium salt (Si-QAS) was synthesized by conjugation of γ-chloropropyl methyl dimethoxysilane and distearic ester of methyldiethanolamine. The chemical structure of the Si-QAS was characterized by using FTIR and 1H NMR. Physicochemical properties of the compound were further investigated and the results showed that the critical micelle concentration of the esterquat was 2.36×10-4 mol.L-1, the corresponding surface tension γCMC was 24.25 mN.m-1, and the standard Gibbs free energy of formation for micellization and adsorption were -30.64 kJ.mol-1 and -56.87 kJ.mol-1, respectively. A mathematical model based on the method of response surface was also established to optimize the conditions of the synthesis process. Microwave power was found to have the strongest effect on synthesis progress and the optimal synthesis conditions were microwave power at 600 W for 20.89 min with a solvent amount of 9.24 g.